Thailand the lessons of protest. - Hewison, Kevin (Asian Studies, 2014)
Since late 2005, Thailand has seen almost unending street protests by red shirts and yellow shirts against incumbent governments. While there are many lessons from this period of often unruly and uncivil political contestation, this paper concentrates on four that bear on several assumptions associated with the broad literature on democratic transitions. These are: (1) the political intransigence of a conservative elite unwilling to accommodate the rise of electoral democracy and subaltern claims for political voice; (2) the challenges posed to notions that the middle class and civil society have certain “historical roles” as the ballast for democratization; (3) the capacity for so-called independent institutions and agencies, created as checks-and-balances to be captured; and (4) the link between high rates of inequality and political rebellion cannot be assumed.